Irritable Bowel Syndrome Novel Concepts for Research and Treatment - Chaban, Victor (IntechOpen, 2016)
This book provides comprehensive and up-to-date insights into emerging trends in research and treatment of irritable bowel syndrome (IBS). Key features include pathogenesis, existing and new therapies, as well as nonpharmacological approach in management of IBS. The authors are known experts who contributed significantly for a better understanding of the etiology of IBS as one of the most commonly diagnosed functional disorders. This book provides a state-of-the-art review of different aspects of IBS and is recommended to healthcare providers, clinical scientists, general practitioners, students, and patients.